ANALISIS KONTRIBUSI EFISIENSI BIAYA PRODUKSI TERHADAP KEMAMPULABAAN PADA PT PERKEBUNAN NUSANTARA VIII JAWA BARAT - Supriatna, Nono (Program Studi Akuntansi FPEB UPI, 2014)
This study is intended to study the magnitude of the contribution of the high efficiency of production costs to the level of profitability of the company, especially in tea commodities empirically by taking the case in PT Perkebunan Nusantara (PTPN) VIII West Java. The findings of this study are expected to contribute thoughts in the management of finance, especially related to the level of efficiency as one of the factors that affect the pampering of the company.The profitability variable is measured by the gross profit margin indiator, while efficiency is measured by comparison between budget and realization. In this study used saturated sampling by examining a number of existing garden units in PTPN VIII West Java Region. The collected data is processed inferential statistically by using simple correlation and regression analysis to test the research hypothesis.From the results of hypothesis testing through regression analysis obtained the findings that the hypothesis proposed in this study accepted empirically, ie efficiency costs roduksi positive effect on kemampulabaan company of 5.2% or contribution of 0.069 units. This means that every increase of 1 value in the variable cost of production efficiency of the company, then the profitability of each unit of the garden will increase by 6.9 units.